Fatal intrusion : a novel - Deaver, Jeffery; Maldonado, Isabella, 1965- (Deaver, Jeffery. Sanchez & Heron, 2024)
"Carmen Sanchez is a tough Homeland Security agent who plays by the rules. But when her sister is attacked, revealing a connection to a series of murders across Southern California, she realizes a conventional investigation will not be enough to stop the ruthless perpetrator. With nowhere else to turn, Sanchez enlists the aid of Professor Jake Heron, a brilliant and quirky private security expert who, unlike Sanchez, believes rules are merely suggestions. The two have a troubled past, but he owes her a favor and she's cashing in. They team up to catch the assailant, who, mystifyingly, has no discernible motive and fits no classic criminal profile. All they have to go on is a distinctive tattoo and a singular obsession that gives this chillingly efficient tactician his nickname: Spider. Over the next seventy-two hours, Sanchez and Heron find themselves in the midst of a lethal chess match with the killer as they race to stop the carnage. As the victims mount, so do the risks. Because this spider's web of intrigue is more sinister--and goes far deeper--than anyone could possibly anticipate"--